Roads to Nowhere in Four States: State and Local Governments in the Atlantic Southeast Facing Sea-Level Rise - Campbell Jones, Shana; Ruppert, Thomas; Deady, Erin; Payne, Heather; Pippin, J. Scott; Huang, Ling-Yee; Evans, Jason M. (Columbia Journal of Environmental Law, 2019)
Coastal communities are becoming increasingly aware of the risks to local infrastructure from more frequent and severe flooding, more extreme storm surges, and sea-level rise. As local governments are responsible for the lion’s share of land use decision-making and infrastructure development in coastal communities in the United States, local governments in the coastal zone will play a key role in adapting to the changing climate. Local decision-makers are facing hard questions about whether to build new infrastructure, adapt existing infrastructure to new standards, continue maintaining existing infrastructure as is, or abandon infrastructure altogether. Monroe County, Florida, for example, has begun to factor sea-level rise considerations into decisions related to road improvement projects, creating specific design standards addressing elevation and working to weigh the benefits and costs of different adaptation options such as elevating roads. Local governments are making these decisions in the context of increasingly unreliable and aging road systems, all while meeting current stormwater criteria which may require drainage improvements. Local decision-makers also are recognizing that crucial infrastructure decisions that directly affect their adaptation success are sometimes out of their control. In the case of the City of Tybee Island, Georgia, for example, tidal flooding restricts access to U.S. Highway 80 on an ever-increasing basis—yet the highway, the only road leading to the island, is not under the city’s jurisdiction but that of the Georgia Department of Transportation. To further complicate matters for local governments, both taking action and failing to act could result in either tort or “takings” liability in cases where a poorly maintained road results in harm to life or loss of property value from diminished access. Using the duty of state and local governments to maintain roads as a focus, this Article explores the complexity of adaptation at the local level as the impacts of climate change become more pronounced. Specifically, this Article presents an analysis of coastal communities in four South Atlantic states—Florida, Georgia, South Carolina, and North Carolina—that are currently facing questions about how to protect property and infrastructure as sea levels rise and flooding increases. This Article distills the findings of an interdisciplinary research project funded by the National Oceanic and Atmospheric Administration (“NOAA”), Florida Sea Grant, Georgia Sea Grant, South Carolina Sea Grant Consortium, and North Carolina Sea Grant. It also consists of a regional analysis comparing how tort and local government law can both further and hinder climate change resilience planning and climate adaptation efforts across these four states. Given that the federal government has offered little in terms of legislation, policy, or funding to direct or support climate adaptation activities, local efforts—and the litigation that inevitably results—are on the forefront of establishing the framework for defining adaptation policy more broadly and influencing the contours of tort and land use law. This Article, therefore, fills an important research gap in existing climate change literature, as it discusses how increased flooding at the local level is putting pressure on traditional conceptions of government duties, immunities, and authorities. This Article also uses roads as a case study to explore how sea-level rise is altering planning, maintenance, and funding for public infrastructure. This discussion focuses on local duties and responsibilities to build, rebuild, modify, or maintain existing roads for two primary reasons: (1) it is a widely shared function among jurisdictions and is the most obvious and visible type of infrastructure to the public, and (2) roads and highways, which are crucial to trade, defense, and nation-building, have long been under the purview of government regulation and funding in the United States. Recently, roads have also become a focal point in local government efforts to address rising sea levels and increased flooding. While sea-level rise may seem like a distant threat, many of its effects are being felt now, as low-lying coastal areas such as Norfolk, Virginia; Brunswick, Georgia; and Monroe County, Florida are experiencing increased nuisance or “sunny day” flooding occurring during seasonal or average high tides. Such flooding typically affects roads, temporarily closing them and increasing maintenance and repair costs. Residents who rely on these roads, often find themselves cut off from their homes, businesses, workplaces, schools, and local hospitals. In this way, sea-level rise and the flooding associated with it have become increasingly familiar and imminent, making roads the “climate change canary in the coal mine” for local governments. Part I of this Article briefly discusses recent sea-level rise issues and coastal science most relevant to the South Atlantic states—North Carolina, South Carolina, Georgia, and Florida. Part II analyzes and compares each state’s road ownership and maintenance duties, first by addressing the threshold question of ownership and jurisdiction, and then by explaining the multi-step analysis that governments must take to evaluate their duties to maintain roads in order to avoid liability. Part II also outlines the wide differences among the four states in our study area and observes a common thread, namely, that in almost each instance, local governments are faced with conflicting pressures that are likely to reward inaction over action and favor short-term political compromises over strategic investments in adaptation. This Part then details how counties and municipalities can discontinue their duties to maintain roads through the process of abandonment and how abandonment can lead to takings liability. Part III offers three proposals for encouraging coordinated adaptation action and protecting local governments that take action to address climate impacts: (1) redefining the scope of the duties that define reasonable conduct for governments in making decisions about public infrastructure in an era of rising sea levels; (2) defining the scope of sovereign immunity protections in a way that encourages innovative and creative decision-making in an era of climate uncertainty; and (3) calling for consistent adaptation duties and authorities at the state level as a crucial first step in mending the regulatory patchwork that currently exists at the state, county, and city levels in our four-state study area. Part IV concludes with a summary of observations and recommended next steps.